Does Boycott Participation Influence Purchasing Decisions for American Beverage Products? - Solikhawati, Anisa; Buchori, Imam; Samsuri, Andriani; Agus Hidayat, Ahmad (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2026)
Geopolitical tensions arising from the Israel-Palestine conflict have intensified boycott movements against American products among Muslim consumers, influencing their purchasing behavior. This study examines the effects of consumer animosity, consumer ethnocentrism, religiosity, and brand image on purchase decisions regarding American beverage products in Surabaya, Indonesia, with boycott participation serving as a moderating variable. A quantitative approach was employed, and data were collected from 270 respondents and analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The findings indicate that consumer animosity and consumer ethnocentrism have significant positive effects on purchase decisions, whereas brand image has a significant negative effect. Religiosity does not significantly influence purchase decisions. Furthermore, boycott participation weakens the relationship between consumer animosity and purchase decisions while strengthening the relationship between consumer ethnocentrism and purchase decisions. However, boycott participation does not significantly moderate the relationships between religiosity and purchase decisions or between brand image and purchase decisions. These findings demonstrate that consumer responses to American beverage products during periods of geopolitical conflict are shaped by a complex interaction of political hostility, ethnocentric tendencies, and boycott participation. The study contributes to the growing literature on consumer behavior in politically sensitive contexts by highlighting the moderating role of boycott participation in shaping purchasing decisions towards foreign products.